Queixas urinárias em mulheres com infarto cerebral: réplica à revisão - Monteiro, Ébe Santos dos; Gimenez, Márcia Maria; Fontes, Sissy Veloso; Fukujima, Márcia Maiumi; Prado, Gilmar Fernandes do (Revista Neurociências, 2009)
.